Experimental Study of the Combined RES-Based Generators and Electric Storage Systems for Public Buildings. (April 2019) - Sahlaoui, K.; Mabrouk, A. Ben; Oueslati, H.; Mabrouk, S. Ben; Cascia, D. La; Zizzo, G.; Favuzza, S.; Massaro, F.; Dusonchet, L.
Abstract: In the present paper, a new approach to the management of energy resources in the Research and Technology Centre of Energy (CRTEn -Tunisia) is proposed and evaluated by the monitoring of a PV installation realized for the cooperation project DE.DU.ENER.T, using renewable energy and economic criteria. The aim of this project is to improve energy efficiency order to minimize the electricity cost consumed at the CRTEn laboratory. According to the bills of electricity received, we noticed that there is a high consumption of electrical current. So, we targeted to install a photovoltaic field of 12KWc to reduce these bills by using the sustainable, green and clean sources. A theoretical study of the PV system sizing realized in order to know in the first hand the compatibility between the different equipment of this installation and to compare the results with those found by the SMA Sunny Design and PV*SOL software in the second hand. The experimental results show that the performance factor of the proposed system is 84.6%. Meanwhile, the cost of the energy generated by the proposed system is 0.045 USD/kWh, which means that the payback period, is about 11 years. The conclusion from this study is that the price of energy generated by PV systems in Tunisia is lower than the subsidized price of energy generated by fossil fuel.